PENYUSUNAN DAN PENERAPAN SISTEM AKUNTANSI DI PDE LAUNDRY - Hendi; Dwi Putri, Nurliana (Politeknik Negeri Sriwijaya, 2024)
Pde Laundry was founded by Mr. Surtaman since 2018 and is still operating until now assisted by 5 employees. This business is located on Jl. Citra Lautan Teduh RT 004 RW 001 No. 2B, Batu Besar, Nongsa, Riau Islands, which operates every day from 07.00 - 17.00 WIB. Pde Laundry provides washing services with a cost of Rp. 7,000 for one kilogram, scrubbing with a cost of Rp. 5,000. With the existence of Pde Laundry is one of the businesses that are easy to run, supported by the City of Batam which many changes/widening of the road that makes people’s clothes become dirty quickly. Laundry business is familiar to the public, so there is a lot of competition between fellow laundry business. So do not be surprised by this, which is to create a characteristic of the laundry business owned. So that the laundry that is owned has more identity and advantages than other laundry. Pde Laundry requires financial reports that can make operational activities run more effectively and efficiently. Thus, Microsoft Access can be used to assist MSMEs in preparing financial reports, the results of which are the Statement of Financial Position, Statement of Profit and Loss, Statement of Changes in Capital, and Statement of Cash Flow